The effect of unemployment on the mental health of spouses: Evidence from plant closures in Germany - Jan Marcus (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
Studies on health effects of unemployment usually neglect spillover effects on spouses. This study specifically investigates the effect of an individual's unemployment on the mental health of their spouse. In order to allow for causal interpretation of the estimates, it focuses on an exogenous entry into unemployment (i.e. plant closure), and combines difference-in-difference and matching based on entropy balancing to provide robustness against observable and time-invariant unobservable heterogeneity. Using German Socio-Economic Panel Study data the paper reveals that unemployment decreases the mental health of spouses almost as much as for the directly affected individuals. The findings highlight that previous studies underestimate the public health costs of unemployment as they do not account for the potential consequences for spouses.
Keywords: I12; J65; 330; unemployment; mental health; plant closure; entropy balancing; matching; job loss; Arbeitslosigkeit; Psychische Störung; Spillover-Effekt; Ehe; Familie; Schätzung; Deutschland